Time management strategies of rock climbers in World Cup bouldering finals - Mckellar, B. J.; Coates, A. M.; Cohen, J. N.; Burr, J. F. (Journal of Human Kinetics, 2023)
Competitive rock climbing recently made its Olympic debut, but minimal published research exists regarding training and competition strategies. Time management strategies define the structured approach climbers take in bouldering competitions to successfully obtain a "top" or a "zone" hold. During finals rounds of the International Federation of Sport Climbing bouldering competitions, climbers are allotted 240 s to complete a boulder. Variables influencing a climber`s time management strategies include their work-to-rest intervals, and the frequency of their attempts or rests. Video analysis of International Federation of Sport Climbing competitions was used to collect time management strategy data of professional climbers. Fifty-six boulders (28 female and 28 male boulders) over the 2019 International Federation of Sport Climbing season were analyzed. Time management strategies variables were compared between slab/slab-like and non-slab bouldering styles using generalized estimating equations with significance set to p < 0.05. Additionally, we determined trends in success rates for various styles of boulders. There were no differences in the number of attempts taken per boulder between slab/slab-like and non-slab boulders (3.7 ± 2.3 and 3.8 ± 2.4, p = 0.97), but climbers spent more time actively climbing on slab/slab-like (92 ± 36 s) compared to non-slab boulders (65 ± 26 s, p < 0.001). Trends in the success rate suggest climbers who take more than 6 attempts on any boulder style are unsuccessful. The results of this study provide practical information that can be used by coaches and athletes to guide training and competition strategy.